Composição química, atividade antimicrobiana, inseticida e antioxidante do óleo essencial e extratos de Myrcia oblongata DC - Santana, Camila Beatriz (2017)
The products of secondary plant metabolism have aroused great economic interest in their chemical diversity and biological activities. The objective of this work was to determine the chemical composition of Myrcia oblongata extracts, to evaluate the antioxidant potential of these extracts, to test the antimicrobial activity against eleven standard microorganisms and ten serotypes of Salmonella spp. Of poultry origin, as well as to evaluate the potential mortality of extracts and essential oil on Alphitobius diaperinus. Saponins, steroids, triterpenoids, tannins and flavonoids have been identified. The extracts presented activity for all microorganisms tested, except for the methanolic extract that did not show activity for P. mirabilis and S. Enteritidis. The hexane extract, ethyl acetate and acetone have antioxidant activity. The essential oil and extracts of hexane, ethanolic, methanolic and ethyl acetate showed high mortality rates on A. diaperinus larvae. For adults, the best results were obtained for essential oil, with a mortality greater than 80%. The results point to the importance of studies to understand the potential and action of plant extracts and essential oils, aiming at reducing the impacts caused by the extensive use of antimicrobials and synthetic antioxidants and by the undue use of chemical substances for pest control.